Clinical characteristics and outcomes of Hodgkin Lymphoma: A single institution retrospective cohort study - Anwar Rjoop; Rania Al-Samama’h; Taima Sari Al-ullemat; Rahaf Alshamali; Batool El-Dwakat; Roaa Al-Saidi; Noor Abdalhakem; Saja Alsarhan; Asmaa Ajarmeh (PLoS ONE, 2026)
Hodgkin lymphoma (HL) is a highly curable B-cell lymphoma, but a group of patients may experience resistance to initial treatment or progress to refractory disease. Moreover, they may experience relapses or long-term complications such as infertility and secondary neoplasms. In this retrospective cohort study, 257 patients diagnosed with HL between 2002 and 2022 were included to identify clinical and laboratory predictors of survival that may contribute to managing patient treatment and follow-up strategies. Demographic, clinical, treatment, and laboratory data at diagnosis were collected from patients’ e-records. Overall survival (OS) and progression-free survival (PFS) were analyzed using Kaplan–Meier curves and log-rank tests. Univariable and multivariable Cox proportional hazards models were used to identify independent predictors of death. The median age at diagnosis was 29 years, with 54.9% males. Nodular sclerosis was the most common subtype (34.6%). Univariable Cox regression analysis showed that high creatinine levels (HR 7.55, 95% CI 2.62–21.81, p < .001), low platelet count (HR 4.87, 95% CI 1.58–14.94, p = .006), and high total bilirubin (HR 3.76, 95% CI 1.34–10.55, p = .012) are factors associated with poor survival. In the exploratory multivariable Cox regression analysis, poor response to treatment was strongly associated with poor survival (HR 7.89, 95% CI 2.39–26.06, p=<.001), followed by low platelet count (HR 4.72, 95% CI 1.28–17.46, p = 0.020). This may suggest that poor treatment response and low platelet count are independent predictors of poor survival in HL patients but require confirmation in a larger cohort. Early detection of high-risk patients based on these clinical and laboratory results may improve patient treatment and follow-up strategies.